The Influence of Competence, Reward System, and Training on the Performance of BPRS Executive Officers with Job Satisfaction as an Intervening Variable - Kartiko, Cahyo; Yuniningsih; Purwanto, Sugeng (Economics and Business Journal (ECBIS), 2025)
This study aims to analyze the effects of competence, reward systems, and training on the performance of executive officers in Sharia Rural Banks (BPRS), with job satisfaction as an intervening variable. The primary focus is to assess the extent to which these factors influence executive performance within the context of Islamic microfinance institutions. Employing a quantitative, explanatory design, primary data were collected via a Likert-scale questionnaire and analyzed using structural equation modeling–partial least squares (SEM–PLS) with SmartPLS. The study population consists of executive officers of BPRS in Indonesia. Using purposive sampling, 121 responses were obtained from multiple BPRS across several regions. The results show that (1) competence has a positive effect on performance; (2) job satisfaction positively affects performance; (3) the reward system influences performance primarily through job satisfaction (partial/competitive mediation), while its direct effect on performance tends to be negative; and (4) training does not exhibit a significant effect on performance, and its indirect path via job satisfaction is not significant. These findings highlight the importance of strengthening competence and redesigning reward systems in alignment with executive expectations to enhance job satisfaction and performance.